Therapeutic vaccination with the Ag85B-Rv2660c-MPT70 fusion protein enhances Mycobacterium tuberculosis H37Ra clearance in post-exposure mice - Hu, Zhiming; Guo, Shaohua; Chen, Wenlong; Ouyang, Jiangshan; Huang, Chunxu; Cao, Ting; Mou, Jun; Gu, Xinxia; Liu, Jie (Frontiers in Immunology, 2025)
Latent tuberculosis infection (LTBI), affecting nearly one-quarter of the global population, represents a major barrier to Tuberculosis (TB) eradication and a paradigm of chronic infectious disease. Current chemotherapeutic regimens for TB, although effective, are limited by drug resistance, toxicity, and poor adherence, underscoring the urgent need for alternative strategies. In this study, we investigated ARM—a recombinant fusion protein comprising Ag85B, Rv2660c, and MPT70—as a therapeutic vaccine in a murine model of post-exposure Mycobacterium tuberculosis (Mtb) infection. ARM immunization elicited robust CD4+ T cell responses, with a higher frequency of polyfunctional T cells producing IFN-γ, and TNF-α compared to the classical BCG vaccine. Critically, ARM also induced strong humoral immunity, marked by elevated Mtb- and ARM-specific IgG levels that enhanced FcγR-dependent phagocytosis, phagosome–lysosome fusion, and intracellular bacterial clearance. ARM-treated mice exhibited reduced pulmonary pathology, improved weight recovery, and superior control of bacterial burden. These findings demonstrate the potential of therapeutic vaccination to mobilize both cellular and antibody-mediated immunity in controlling Mtb infection and offer a broader immunological strategy for managing chronic infectious diseases. ARM represents a promising candidate for post-exposure TB vaccination, with potential to enhance bacterial clearance and reduce disease progression in high-burden populations.